Marine cosmeceuticals : trends and prospects - Kim, Se-Kwon (CRC Press, 2012)
"The first comprehensive volume on marine cosmeceuticals, this book covers their sources and prospects; extraction; isolation; identification; structure and chemical composition; and in vivo and in vitro applications. It covers fundamentals as well as practical techniques in the emerging field of marine cosmeceuticals. This reference enables researchers in cosmetic science and natural product chemistry to identify new outlets for the new compounds that they isolate. It makes the case for using natural compounds from the sea to replace synthetic, toxic cosmetics. It also discusses the application of these products on ailments such as skin disease, diabetes, and arthritis"--Vydavatelská anotace
Keywords: přírodní kosmetické přípravky; kosmetické přípravky; lékařská kosmetika; mořská biologie; mořští živočichové; mořské řasy; mořské rostliny; biochemie; natural cosmetics; cosmetics; medical cosmetics; marine biology; sea animals; seaweeds; sea plants; biochemistry; sborníky; miscellanea